Financial sustainability of cultural heritage: A review of crowdfunding in Europe - Daniela Angelina Jelinčić; Marta Šveb (Journal of Risk and Financial Management, 2021)
Most cultural heritage projects strive in ensuring financial sustainability, mainly relying on public subsidies. At the same time, they lack fund management policies which directly affects their financial sustainability. European Union heritage policies focus on sustainability but after investments have been made, there are rare cases which can boast about it. A number of heritage funding mechanisms exist which are explained in this review paper, while the focus is on crowdfunding as an alternative mechanism. The study used literature review method based on PRISMA guidelines to analyze new trends and suitability of crowdfunding for cultural heritage projects, and to detect possible factors influencing its success. The purpose was to add to the existing knowledge while offering a systematic review which can be applied in practice. Findings indicate the trend of participatory approach to heritage, which is in line with the participatory nature of crowdfunding campaigns. Further, crowdfunding suitability for cultural heritage projects was confirmed while its success factors majorly depend on the policy framework, heritage project nature and management of the campaign itself.
Keywords: 330; crowdfunding; cultural heritage; Europe; financial sustainability